Morphometric and Hidrological Characteristics of Way Apu Watershed Regency Of Buru - Rafael M. Osok; Silwanus M. Talakua; Alfredo Manusama; Pieter J. Kunu (Faculty of Agriculture, Pattimura University, 2020)
Morphometry is important characteristics to understand hydrological processes of a catchment.The research purpose was to study the morphometry and flood discharge characteristics of the Way Apu Watershed. Morphometrics data were measured using topographic maps and SIG-ArcView. The frequency distribution of rain was calculted using the Log-Pearson Type III, Gumbel, Normal, Log-Normal methods, and the design rainfall was determined according to 2, 5, 10, 25, 50, and 100 years return periods. The flood discharge was calculated using the rational method, while the hydrograph unit was established using the Nakayasu method. The result showed that the watershed roundness ratio is 0.46 and the elongated ratio is 0.86 indicating the elongate watershed form. The design Rainfall of the return periods of 2, 5, 10, 20, 25, 50 and 100 years range from 37.59 - 185.14 mm (Log Pearson Type III), 41.32 - 180.28 mm (Gumbel), 47, 68 - 139,98 mm (Normal), and 36,82 - 203,66 mm (Log-Normal). The Smornov-Kolmogorof test results show that the Log-Pearson Type III, Gumbel, and Log-Normal methods are suitable to calculate the design flood discharge. Data of the design flood discharge of Gumbel is suited for 25 years of waterwork plan, while Log-normal is suited for 100 years plan. Based on the Nakayasu Synthetic Hydrograph Unit, the river capacity of the Way Apu watershed is 21.37 m3/sec.